Tradisi Manyanda di Nagari Talang Kabupaten Solok pada Karya Tari "Seratus" dalam Manyaratuih Hari - Iffah Zaaidah; Syahril Syahril; Adjuoktoza Rovylendes; Dony Osmond (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work "SERATUS" is inspired by the Manyanda tradition, which has several stages, one of which is the manyaratuih hari (the traditional wedding ceremony). This stage involves a dowry procession performed by both the groom and the bride. In this work, the artist attempts to interpret the dowry procession for both parties, while also depicting the customary penalty of the death of a cat, which the family faces if they fail to follow the Manyanda tradition. The dance work "SERATUS" is realized using props inspired by the dowry forms used in the tradition. The methods used in the creation process include data collection and field observation, exploration, improvisation, forming, and evaluation. This work is performed by eight dancers and supported by eight supporting dancers. The work uses a dramatic style with a social theme, reinforced by the use of live techno music as accompaniment, thus supporting the dramatic flow in line with the artist's concept.